ANALISIS JALUR KRITIS PEKERJAAN BETON PRECAST LONG BEAM PADA PEKERJAAN DERMAGA DI MAKASSAR NEW PORT MENGGUNAKAN METODE PERT - Damayanti, Rosa; Ashury, Ashury (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2022)
In a construction activity, there are several aspects that require proper management and processingrequired to have accuracy, determination, performance, accuracy, and safety to produce the appropriate endwith expectations. In a project, it is necessary to handle good scheduling management. Because ofTherefore, it needs to be handled with careful and thorough calculations so that no mistakes occur when the project is in progressjust lasts. The duration of a project does not have to add up the total time of the activity,but enough to find the critical path. Scheduling a project is an outcome factor that canprovide information about the schedule plan and progress of the project. In this case, the resource performance iscosts, personnel, equipment and materials, and project duration planning. When working on a project,problems often arise, namely the project implementation time does not match the agreed time. MatterThis will have a negative impact on the company. As a result, when a project is not well planned,Project implementation involves each other throughout a series of activities that will influence each other.